Developing Organizational Members' Communicative Abilities A Rationale for Specific Methods - Sypher, Beverly Davenport; Roberts, Rona ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Because the skills needed for organizational effectiveness are typically communication based, many methods are available for communication trainers, including techniques originally designed to identify other cognitive and behavioral skills. The successful communication trainer can use these methods and measures, along with those directly aimed at improving communication abilities, to increase organizational participants' skills in perspective taking, self-monitoring, listening, and designing appropriate messages. Self-generated case studies and inventories are effective in organizations like juvenile court staffs, county government administration, insurance and manufacturing companies, and engineering firms, and are more effective with groups of members and longer-term training projects. Role playing and coaching can be used to develop listening and perception skills, and are more useful in shorter training programs, although the coaching method demands a longer investment of time and money. Because of a lack of evaluative methodology and because many programs are tailored to specific organizations, the effectiveness of each method is difficult to ascertain. (CRH)
ERIC Note: Paper presented at the Annual Meeting of the Southern Speech Communication Association (Baton Rouge, LA, April 5-7, 1984).
Educational level discussed: Higher Education.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Modification; Behavior Theories; Communication Apprehension; Communication Skills; Communication (Thought Transfer); Education Work Relationship; Higher Education; Interpersonal Competence; On the Job Training; Organizational Communication; Organizational Development; Organizations (Groups); Speeches/Meeting Papers; Guides, Classroom -- Teacher